The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1186/s13568-018-0593-4
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and characterization of phosphofungi, and screening of their plant growth-promoting activities

Abstract: Rhizospheric microorganisms can increase phosphorus availability in the soil. In this regard, the ability of phosphofungi to dissolve insoluble phosphorus compounds is greater than that of phosphate-solubilizing bacteria. The aim of the current study was to identify efficient phosphofungi that could be developed as commercial microbial agents. Among several phosphate-solubilizing fungal isolates screened, strain CS-1 showed the highest phosphorus-solubilization ability. Based on phylogenetic analysis of the in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
27
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 59 publications
(33 citation statements)
references
References 52 publications
3
27
0
3
Order By: Relevance
“…Ten pots were treated with the same amount of sterile Milli-Q water (20 ml) and marked as the blank control group, CK ( Wei et al., 2017 ). Randomized complete block design was used in this study ( Wang et al., 2018 ). After 30 days of cultivation, wheat plants were taken out of the pots and plant biomass was measured.…”
Section: Methodsmentioning
confidence: 99%
“…Ten pots were treated with the same amount of sterile Milli-Q water (20 ml) and marked as the blank control group, CK ( Wei et al., 2017 ). Randomized complete block design was used in this study ( Wang et al., 2018 ). After 30 days of cultivation, wheat plants were taken out of the pots and plant biomass was measured.…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, CO 2 emission variation in CS and CB needs further exploration. Gibberella and Monographella, which cause soil-borne diseases in crops (Tatagiba et al 2016;Wang et al 2018;Yan et al 2018), were lower in CS and CB in the 0-20 cm layer, with their levels in CB exhibiting significant differences relative to those in CF (p < 0.05). These reduced pathogenic fungal contents might lessen the probability of morbidity.…”
Section: Discussionmentioning
confidence: 98%
“…actinomyces, bacteria, fungi, and yeasts have been screened for phosphate solubilization. They were shown to enhance the solubilization of insoluble P compounds ( Gizaw et al, 2017 ; Nandimath et al, 2017 ; Mohamad et al, 2018 ; Wang et al, 2018 ; Chen and Liu, 2019 ; Liu et al, 2019 ). For fungi, Rhizopus stolonifer var.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies of PSF identified fungal species names based on morphology, highest nucleotide similarity in MegaBLAST searches of NCBI’s GenBank nucleotide database and/or phylogenetic analysis of ITS sequence data ( Nelofer et al, 2015 ; Wang et al, 2018 ; Zhang et al, 2018 , Supplementary Table S5 ). However, these are insufficient to determine the species names, especially within species complexes ( Samson et al, 2014 ; Doilom et al, 2017 ; Hyde et al, 2020a , b ).…”
Section: Discussionmentioning
confidence: 99%